Comprehensive Analysis of Land Use and Land Cover Shifts from A Redd Perspective: A Case Study of Banepa Municipality, Nepal - Ghimire, Sujan; Poudel, Hemanta; Upadhyaya, Sharad; Adhikari, Binod Kumar (Nepal Journal of Multidisciplinary Research, 2023)
This paper examines the dynamic changes in land use and cover in Banepa Municipality over three decades, from 1991 to 2021, using the remote sensing method within the REDD perspective. It uncovers an 11% surge in built-up areas and a 5% decline in forest cover, with minimal agricultural fluctuations (1%) and a substantial 7% decrease in barren land. Urgent concerns about ecological balance prompt a call for immediate REDD implementation. To address these issues, the study advocates for employing monitoring methods, including remote sensing, to evaluate forest and land resources. This data can inform comprehensive studies on the drivers of deforestation and forest degradation, alongside feasibility and sectorial analyses, including cost-benefit assessments for effective land-use planning. The conclusion stresses the imperative need for planned urban development in Banepa to preserve open spaces, forests, and agriculture. This study provides vital insights into the intricate relationship between land-use changes and climate impact, emphasizing the urgency of sustainable development actions.